Impact of the biological control agent gyranusoidea tebygi noyes (Hymenoptera: Encyrtidae) on the mango mealybug, rastrococcus invadens williams (Homoptera: Pseudococcidae), in Benin - Bokonon-Ganta, A.H.; Neuenschwander, P. (1995)
The distribution of Rastrococcus invadens among different host plants and the impact of the pseudococcids on mango growth were investigated on 2067 trees in 3 surveys across all the ecological zones of Benin. The first survey started in 1987, less than 1 year after the first release of the exotic parasitoid Gyranusoidea tebygi. Within 3 years, G. tebygi had colonized the entire area of infestation, and was found on practically all infested mango trees as well as other infested host plants. By 1991, the incidence of R. invadens on the secondary host plants had declined significantly. The percentage of infested mango trees declined from 31% in 1989 to 17.5% in 1991, with largest populations being found in coastal savanna. During the same period, the mean percentage of infested mango trees having indigenous predators declined from 42.3 to 20.9%. Average pseudococcid densities declined steadily from 9.7 females/48 leaves in 1989, with 3.2% of all mango trees having densities above 100 pseudococcids, to 6.4 females/48 leaves in 1991, with 1.3% of all trees having densities above 100 pseudococcids. In multiple regression analyses, based on 23 meteorological, agronomic and plant variables, the duration of the parasitoid's presence proved to be the major factor. It influenced pseudococcid population densities and sooty mould incidence, which in turn, affected the production of new leaves. In all analyses, the impact of rainfall, for example, on the sooty mould or the pseudococcid was less important than the effect of G. tebygi. The present study demonstrates for the first time on a large scale the impact of G. tebygi on R. invadens and, indirectly, on its main host plant, mango.